Determinants of knowledge on HIV/AIDS among women in Bhutan a study based on Bhutan multiple inidcator survey, 2010 - Wangdi, Lekey
This study assesses the determinants of knowledge on HIV/AIDS among Bhutanese women using data from the Bhutan Multiple Indicator Survey, a national representative survey covering all 20 districts (Dzongkhags) and 205 sub-districts (Gewogs). While 84 percent of women have heard about HIV/AIDS, they do not demonstrate high level of knowledge about it. Knowledge among women on HIV/AIDS using nine questions in the survey shows a mean correct knowledge score of 5.6 out of a total 9.0. Misconception are common where two-third of the women believe that one can get infected with HIV from mosquito bites and a healthy looking person cannot have AIDS. Never married women, those with higher education, better socio economic status and from the western region of the country have higher level of knowledge in HIV/AIDS while age and place of residence did not prove to be significant determinants of knowledge. The study found that the strongest predictors of knowledge on HIV/AIDS are education and socio-economic status.